Plastic lens

By using heat-resistant acrylic resin and silicon oxide basecoat in plastic lenses and using alternately stacked anti-reflection layer structures, the problems of insufficient durability of existing plastic lenses and difficulty in surface shape control in high temperature and high humidity environments are solved, and efficient and durable lens production is achieved.

CN119535651APending Publication Date: 2025-02-28ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411209136.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-31
Filing Date
2024-08-30
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing plastic lenses are not durable in high temperature and high humidity environments, and the wet film formation method makes it difficult to control surface shape and low productivity.

Method used

A heat-resistant acrylic resin is used as the lens body, and a base coat layer composed of silicon oxide and an anti-reflection layer stacked alternately with a high-refractive index film and a low-refractive index film are formed on the lens body, and the film formation is achieved by vacuum evaporation.

Benefits of technology

It improves the durability and productivity of plastic lenses, ensures good performance in high temperature and high humidity environments, and achieves high control of the opposite shape.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119535651A_ABST
    Figure CN119535651A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide a plastic lens having excellent productivity and further improved durability. The present invention provides a plastic lens provided with a lens main body, an undercoat layer covering at least one optical effective surface of the lens main body, and an antireflection layer covering the undercoat layer from the opposite side to the lens main body, the lens main body comprising a heat-resistant acrylic resin, the undercoat layer comprising a silicon oxide SiOx (1 < x < 2), and the antireflection layer comprising a silicon oxide SiOx (1 < x < 2). The refractive index of the undercoat layer at a wavelength of 500 nm is 1.60 or more and 1.70 or less, and the thickness of the undercoat layer is greater than 300 nm and less than 1000 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a plastic lens. Background Art

[0002] Acrylic resins represented by polymethyl methacrylate (PMMA) are used as optical materials, etc., from the viewpoints of high transparency, low birefringence, light stability, etc. For example, Patent Document 1 discloses a plastic lens having an antireflection film formed on the surface of a PMMA substrate.

[0003] In recent years, acrylic resins with excellent heat resistance have been disclosed in response to the demand for using acrylic resins in parts such as surveillance cameras and vehicle-mounted cameras that are used in harsh environments such as high temperature and high humidity and require stronger durability than before. For example, Patent Document 2 discloses a plastic lens using an acrylic resin with excellent heat resistance as a base material.

[0004] Prior art literature

[0005] Patent document 1: Japanese Patent Application Laid-Open No. 6-273601.

[0006] Patent document 2: International Publication No. 2023 / 074597. Summary of the invention

[0007] Regarding the method of forming a film on a resin substrate, it is generally known that the shape accuracy of the film-forming surface in the wet film-forming method is much worse than that in the dry film-forming method such as evaporation. The research results of the present inventors show that in the plastic lens described in Patent Document 2, a hard coating layer is formed between the substrate composed of acrylic resin and the anti-reflection layer by the wet film-forming method, and therefore, it cannot cope with the application requiring a high degree of control of the surface shape. In addition, since the coating, drying, and curing steps of the hard coating layer are required between the molding process of the lens substrate and the film-forming process of the anti-reflection layer, there is also a problem of poor productivity.

[0008] On the other hand, the plastic lens described in Patent Document 1 forms an anti-reflection film on the surface of the substrate by vacuum evaporation, which is a dry film forming method. However, since PMMA as the substrate has low heat resistance, there is a problem that it cannot fully cope with the durability required by vehicle-mounted cameras, etc. In recent years, such stronger durability has been widely required in addition to vehicle-mounted applications, and both the substrate and the anti-reflection film need to have improved durability.

[0009] Therefore, an object of the present invention is to provide a plastic lens having excellent productivity and further improved durability.

[0010] That is, the present invention is as follows.

[0011] [1] A plastic lens comprising a lens body, a primer coating covering an optically effective surface of at least one surface of the lens body, and an antireflection layer covering the primer coating from a side opposite to the lens body, wherein the lens body comprises a heat-resistant acrylic resin, and the primer coating comprises silicon oxide SiO x (1<x<2), the refractive index of the primer layer at a wavelength of 500 nm is greater than 1.60 and less than 1.70, and the thickness of the primer layer is greater than 300 nm and less than 1000 nm.

[0012] [2] The plastic lens according to [1], wherein the thickness of the primer layer is greater than 300 nm and less than 800 nm.

[0013] [3] A plastic lens as described in [1] or [2], wherein the antireflection layer is a layer formed by alternating stacking of a high refractive index film and a low refractive index film, the high refractive index film is composed of a high refractive index material, the low refractive index film is composed of a low refractive index material, the high refractive index material is any one or more of titanium oxide and zirconium oxide, and the low refractive index material is silicon oxide having a refractive index lower than that of the primer layer at a wavelength of 500 nm.

[0014] [4] The plastic lens according to any one of [1] to [3], wherein the heat-resistant acrylic resin has a glass transition temperature of 116° C. or higher.

[0015] [5] A plastic lens as described in any one of [1] to [4], wherein the heat-resistant acrylic resin contains a structural unit having a ring structure in its structure, and the structural unit having a ring structure contains one or more selected from the group consisting of a cyclic imide structural unit, an aromatic vinyl structural unit, an alicyclic vinyl structural unit and a lactone ring structural unit, and the proportion of the structural unit having a ring structure in the heat-resistant acrylic resin is 15% by mass or more.

[0016] According to the present invention, it is possible to provide a plastic lens having excellent productivity and further improved durability. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a schematic diagram showing a cross section parallel to the optical axis Z and including the optical axis Z, for an example of the plastic lens (plano-convex lens) according to the present embodiment.

[0018] Figure 2 (a) is a schematic structural diagram (front view) of a typical vapor deposition device having a resistance heating type vapor deposition source, Figure 2 (b) is a schematic structural diagram (front view) of a typical vapor deposition device having an electron beam heating type vapor deposition source.

[0019] Description of Reference Numerals

[0020] P: Plastic lens.

[0021] P1: Lens body.

[0022] P2: Base coating.

[0023] P3: Anti-reflection layer.

[0024] Sa, Sb: optically effective surfaces.

[0025] Z: optical axis.

[0026] 11: Evaporation device.

[0027] 12: Chamber.

[0028] 13: Resistance heating power supply.

[0029] 14: Evaporation cover.

[0030] 15: Boat.

[0031] 16: Baffle.

[0032] 17: Evaporation material.

[0033] 18: Substrate for film formation.

[0034] 19: Film.

[0035] 20: Evaporation device.

[0036] 21: Chamber.

[0037] 22: Electron gun.

[0038] 23: Electron gun power supply.

[0039] 24: Evaporation cover.

[0040] 25: Crucible.

[0041] 26: Pole piece.

[0042] 27: Baffle.

[0043] 28: Reflecting electron trap.

[0044] 29: Evaporation material.

[0045] 30: Substrate on which film is to be formed.

[0046] 31: Film.

[0047] 32: Electron beam.

[0048] 33: Reflected electrons. DETAILED DESCRIPTION

[0049] Hereinafter, a mode for carrying out the present invention (hereinafter referred to as “the present embodiment”) will be described in detail, but the present invention is not limited to the following description and can be carried out with various modifications within the scope of the gist thereof.

[0050] In addition, hereinafter, regarding the polymer forming the heat-resistant acrylic resin contained in the plastic lens of the present embodiment, the structural unit constituting the polymer is referred to as "-monomer unit" and / or "-structural unit" containing a plurality of the "-monomer units".

[0051] In addition, regarding the constituent material of the "-monomer unit", the "unit" may be omitted and the material may be simply referred to as "-monomer".

[0052] <Plastic lens>

[0053] The plastic lens of this embodiment can be any one of a biconvex lens, a plano-convex lens, a meniscus lens, a biconcave lens, a plano-concave lens, a plane lens, a cylindrical lens, a Fresnel lens, a biconvex lens, a fly-eye lens, a lens array, a microlens array, a prism lens, etc.

[0054] Hereinafter, the plastic lens according to the present embodiment will be described with reference to the drawings.

[0055] Figure 1 This is a schematic diagram showing a cross section parallel to and including the optical axis Z of an example of the plastic lens (plano-convex lens) according to the present embodiment.

[0056] The plastic lens P of this embodiment at least comprises a lens body P1 made of resin, a primer layer P2 covering an optically effective surface of at least one surface of the lens body (plastic lens substrate) P1, and an anti-reflection layer P3 covering the primer layer P2 from the side opposite to the lens body P1. That is, for the plastic lens P of this embodiment, the primer layer P2 and the anti-reflection layer P3 are sequentially stacked on the optically effective surface of the lens body P1.

[0057] The plastic lens P of this embodiment may include other layers such as an antifouling layer for making the surface of the plastic lens P difficult to be contaminated and a gas barrier layer for suppressing the penetration of water vapor into the plastic lens P, in addition to the primer layer P2 and the antireflection layer P3.

[0058] It should be noted that, in the present invention, an optically effective surface refers to a surface or interface that exerts any optical effect such as refraction or reflection on the light or light beam incident on the surface. Figure 1 In the plastic lens P, the optically effective surfaces of the lens body P1 are the surface Sa and the surface Sb. The surface Sa is an aspherical surface with a curvature radius R, and the surface Sb is a flat surface (with a curvature radius of ∞). Figure 1 The plastic lens P of FIG. 1 is an example in which only the optically effective surface Sa is covered by the primer layer P2. Figure 1 As shown, only one of the plurality of optically effective surfaces may be covered with the primer layer P2 and the antireflection layer P3, or two or more optically effective surfaces may be covered with the primer layer P2 and the antireflection layer P3.

[0059] In the method for manufacturing the plastic lens P, as described later, after the lens body P1 is molded, a primer layer forming step of forming the primer layer P2 and an antireflection layer forming step of forming the antireflection layer P3 are performed.

[0060] <Lens body P1>

[0061] The lens body P1 includes a heat-resistant acrylic resin. The “heat-resistant acrylic resin” refers to an acrylic resin having heat resistance, and “having heat resistance” means that the value of the Vicat softening temperature measured according to ISO 306B50 is 110° C. or higher.

[0062] The heat-resistant acrylic resin may be used alone or in combination of two or more.

[0063] [Heat-resistant acrylic resin]

[0064] The heat-resistant acrylic resin contained in the lens body P1 preferably has a glass transition temperature (Tg) of 115° C. or higher, more preferably 116° C. or higher, further preferably 117° C. or higher, and particularly preferably 118° C. or higher, when measured in accordance with JIS-K7121, from the viewpoint of durability. In addition, in consideration of the moldability of the lens body P1, etc., the glass transition temperature Tg is preferably 200° C. or lower, more preferably 180° C. or lower, and further preferably 160° C. or lower.

[0065] The acrylic resin is a polymer containing an ethylenically unsaturated monomer having at least one carboxyl group or carboxylate group as a monomer component, and the acrylic resin may be a homopolymer or copolymer of the ethylenically unsaturated monomer, or a copolymer of the ethylenically unsaturated monomer and other copolymerizable monomers.

[0066] Examples of the ethylenically unsaturated monomer having a carboxyl group or a carboxylate group include methacrylic acid, acrylic acid, methacrylic acid esters, and acrylic acid esters.

[0067] The heat-resistant acrylic resin contained in the lens body P1 preferably has a ring structure in its structure. More specifically, it is preferably a heat-resistant acrylic resin having a structural unit having a ring structure in its structure, and preferably, the structural unit having a ring structure includes at least one structural unit of a cyclic imide structural unit, a lactone ring structural unit, an aromatic vinyl structural unit, and an alicyclic vinyl structural unit.

[0068] The structural unit having a ring structure may be used alone or in combination of two or more.

[0069] Taking the heat-resistant acrylic resin as 100 mass %, the ratio of the structural unit having a ring structure in the heat-resistant acrylic resin is preferably 15 mass % or more, more preferably 16 mass % or more, further preferably 17 mass % or more, and particularly preferably 18 mass % or more. If the ratio of the ring structure is within the above range, it is preferred from the viewpoints of heat resistance, low birefringence, scratch resistance, and moldability.

[0070] Examples of the cyclic imide structural unit constituting the heat-resistant acrylic resin include a maleimide structural unit and a glutarimide structural unit.

[0071] (Maleimide structural unit)

[0072] As the maleimide structural unit constituting the heat-resistant acrylic resin, a structural unit represented by the following general formula (1) is preferred.

[0073] Chemical formula 1

[0074]

[0075] In the general formula (1), R 1 It represents any one selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, a cycloalkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, and an aryl group having 6 to 12 carbon atoms, and the alkyl group, alkoxy group, cycloalkyl group, and aryl group may have a substituent on the carbon atom.

[0076] The monomers for forming the maleimide structural unit are not particularly limited, and examples thereof include maleimide; N-alkyl-substituted maleimides such as N-methylmaleimide, N-ethylmaleimide, and N-cyclohexylmaleimide; and N-aryl-substituted maleimides such as N-phenylmaleimide, N-methylphenylmaleimide, N-ethylphenylmaleimide, N-butylphenylmaleimide, N-xylylmaleimide, N-hydroxyphenylmaleimide, N-methoxyphenylmaleimide, N-(o-chlorophenyl)maleimide, N-(m-chlorophenyl)maleimide, and N-(p-chlorophenyl)maleimide.

[0077] As for the above-mentioned monomers, from the viewpoint of imparting heat resistance and moist heat resistance, preferred examples include N-cyclohexylmaleimide, N-phenylmaleimide, N-methylphenylmaleimide, N-(o-chlorophenyl)maleimide, N-(m-chlorophenyl)maleimide, and N-(p-chlorophenyl)maleimide. From the viewpoint of easy availability and imparting heat resistance, more preferred examples include N-cyclohexylmaleimide and N-phenylmaleimide. Even more preferred example includes N-phenylmaleimide.

[0078] The maleimide structural units may be used alone or in combination of two or more.

[0079] From the viewpoint of heat resistance, molding processability, optical properties, and color tone stability, the content of the maleimide structural unit is preferably 0 to 50% by mass, more preferably 2 to 40% by mass, and even more preferably 5 to 30% by mass, based on 100% by mass of the heat-resistant acrylic resin.

[0080] In addition, in this invention, the content of the structural unit which comprises a heat-resistant acrylic resin can be calculated|required by the method described in the Example mentioned later.

[0081] (Glutarimide structural unit)

[0082] The glutarimide structural unit constituting the heat-resistant acrylic resin may be formed after the resin is polymerized. As the glutarimide structural unit, a structural unit represented by the following general formula (2) is preferred.

[0083] Chemical formula 2

[0084]

[0085] In the general formula (2), R 1 and R 2 Each independently represents a hydrogen atom or a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, and the alkyl group may be substituted with, for example, a hydroxyl group.

[0086] In addition, R 3 It represents any one selected from the group consisting of a hydrogen atom, a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, and a substituted or unsubstituted aryl group having 6 to 18 carbon atoms.

[0087] It is particularly preferred that R 1 , R 2 and R 3 All are methyl.

[0088] The glutarimide structural units may be used alone or in combination of two or more.

[0089] From the viewpoint of heat resistance, molding processability and optical properties, the content of the glutarimide structural unit is preferably 0 to 50% by mass, more preferably 2 to 40% by mass, and even more preferably 5 to 30% by mass, based on 100% by mass of the heat-resistant acrylic resin.

[0090] The glutarimide structural unit can be obtained by the following well-known methods: a method of copolymerizing (meth)acrylate and / or (meth)acrylic acid and then reacting ammonia or amine with urea or unsubstituted urea under high temperature conditions; a method of reacting a methyl (meth)acrylate-styrene copolymer with ammonia or amine; a method of reacting a poly(meth)acrylic anhydride with ammonia or amine, etc.

[0091] Specifically, there can be mentioned the method described in US Pat. No. 4,246,374 to RM Kopchik.

[0092] The glutarimide structural unit can also be formed by imidizing an acid anhydride such as maleic anhydride, a half ester of the acid anhydride and a linear or branched alcohol having 1 to 20 carbon atoms, or an α,β-ethylenically unsaturated carboxylic acid.

[0093] Furthermore, another preferred production method is a method of obtaining a resin containing the glutarimide structural unit by polymerizing a (meth)acrylate and, if necessary, an aromatic vinyl monomer and other vinyl monomers, followed by imidization reaction.

[0094] In the process of the imidization reaction, an imidization agent can be used, and a ring closure accelerator can be added as needed. Here, as the imidization agent, ammonia or a primary amine can be used. As the primary amine, methylamine, ethylamine, n-propylamine, cyclohexylamine, etc. can be preferably used.

[0095] As the method for implementing imidization reaction, there is no particular limitation, and a conventionally known method can be used, for example, a method using an extruder, a transverse twin-shaft reaction device or a batch reaction tank can be cited. As the extruder, there is no particular limitation, and a single-shaft extruder, a twin-shaft extruder or a multi-shaft extruder can be preferably used. More preferably, a tandem type reaction extruder formed by arranging two twin-shaft extruders in series can be used.

[0096] In addition, when producing the above resin, in addition to the above imidization step, an esterification step of treating the carboxyl group of the resin with an esterification agent such as dimethyl carbonate can be included. In this case, a catalyst such as trimethylamine, triethylamine, or tributylamine can also be used in combination.

[0097] The esterification step can be performed similarly to the above-mentioned imidization step, for example, by using an extruder or a batch reaction tank.

[0098] In addition, it is preferred that a vent capable of reducing the pressure to below atmospheric pressure be installed in the apparatus used for the purpose of removing excess esterification agent, by-products such as methanol, or monomers.

[0099] (Lactone ring structural unit)

[0100] The lactone ring structural unit constituting the heat-resistant acrylic resin may be formed after the resin is polymerized. As the lactone ring structural unit, a structural unit represented by the following general formula (3) is preferred.

[0101] Chemical formula 3

[0102]

[0103] In the general formula (3), R 1 , R 2 and R 3 Each independently represents a hydrogen atom or an organic group having 1 to 20 carbon atoms. The organic group may also contain an oxygen atom.

[0104] The lactone ring structural units may be used alone or in combination of two or more.

[0105] From the viewpoint of heat resistance, moldability and optical properties, the content of the lactone ring structural unit is preferably 0 to 50% by mass, more preferably 2 to 40% by mass, and even more preferably 5 to 30% by mass based on 100% by mass of the heat-resistant acrylic resin.

[0106] The method for forming the heat-resistant acrylic resin containing a lactone ring structural unit is not particularly limited, and an example thereof includes a method in which a monomer having a hydroxyl group in a side chain (e.g., a monomer having a structure represented by the following general formula (4) (such as methyl 2-(hydroxymethyl)acrylate)) is copolymerized with a monomer having an ester group such as a (meth)acrylate monomer, and then the obtained copolymer is heat-treated in the presence or absence of a predetermined catalyst to introduce a lactone ring structure into the polymer.

[0107] Chemical formula 4

[0108]

[0109] In the general formula (4), R 1 The group represents a hydrogen atom or a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, and the alkyl group may be substituted with, for example, a hydroxyl group.

[0110] R 2 It represents a group having 1 to 12 carbon atoms, preferably a hydrocarbon group having 1 to 12 carbon atoms, and the hydrocarbon group may be substituted with, for example, a hydroxyl group.

[0111] It is particularly preferred that R 1 is a hydrogen atom, R 2 It's methyl.

[0112] Furthermore, as long as the effects of the present invention can be exhibited, the monomer having the structure represented by the general formula (4) may remain in the heat-resistant acrylic resin in an unreacted form.

[0113] (Aromatic vinyl structural unit)

[0114] As the aromatic vinyl structural unit constituting the heat-resistant acrylic resin, it is preferable to use a structural unit derived from an aromatic vinyl monomer represented by the following general formula (5).

[0115] Chemical formula 5

[0116]

[0117] In the general formula (5), R 1 The group represents a hydrogen atom or a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, and the alkyl group may be substituted with, for example, a hydroxyl group.

[0118] R 2 is any one selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an aryl group having 6 to 8 carbon atoms, and an aryloxy group having 6 to 8 carbon atoms, and R 2 All of them may be the same group or different groups. 2 They can also form a ring structure with each other.

[0119] n represents an integer of 0-5.

[0120] The monomer for forming the aromatic vinyl structural unit is not particularly limited, and examples thereof include styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, 3,4-dimethylstyrene, 3,5-dimethylstyrene, p-ethylstyrene, m-ethylstyrene, o-ethylstyrene, p-tert-butylstyrene, 1-vinylnaphthalene, 2-vinylnaphthalene, 1,1-diphenylethylene, isopropenylbenzene (α-methylstyrene), isopropenyltoluene, isopropenylethylbenzene, isopropenylpropylbenzene, isopropenylbutylbenzene, isopropenylpentylbenzene, isopropenylhexylbenzene, and isopropenyloctylbenzene.

[0121] Among the above, styrene and isopropenylbenzene are preferred, and styrene is more preferred from the viewpoints of imparting fluidity and reducing unreacted monomers by increasing the polymerization conversion rate.

[0122] In the heat-resistant acrylic resin of the present embodiment, these can be appropriately selected according to the required properties.

[0123] The aromatic vinyl structural units may be used alone or in combination of two or more.

[0124] From the viewpoint of heat resistance, moldability and optical properties, the content of the aromatic vinyl structural unit is preferably 0 to 50% by mass, more preferably 2 to 40% by mass, and even more preferably 4 to 30% by mass, based on 100% by mass of the heat-resistant acrylic resin.

[0125] (Alicyclic vinyl structural unit)

[0126] The alicyclic vinyl structural unit constituting the heat-resistant acrylic resin can be formed after the resin is polymerized. As the alicyclic vinyl structural unit, a structural unit represented by the following general formula (6) is preferably used.

[0127] Chemical formula 6

[0128]

[0129] In the general formula (6), R1 to R3 each independently represent a hydrogen atom, a chain hydrocarbon group, a halogen atom, an alkoxy group, a hydroxyl group, an ether group, an ester group, a cyano group, an amide group, an imide group, a silyl group, and any one of a chain hydrocarbon group substituted by a polar group (halogen atom, alkoxy group, hydroxyl group, ether group, ester group, cyano group, amide group, imide group or silyl group). Among them, a hydrogen atom or a chain hydrocarbon group having 1 to 6 carbon atoms has excellent heat resistance and low water absorption, and is therefore preferred. As the halogen atom, a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom can be cited. As the chain hydrocarbon group substituted by a polar group, for example, a halogenated alkyl group having 1 to 20 carbon atoms, preferably 1 to 10, and more preferably 1 to 6 carbon atoms can be cited. Examples of the chain hydrocarbon group include an alkyl group having 1 to 20 carbon atoms, preferably 1 to 10 carbon atoms, and more preferably 1 to 6 carbon atoms; and an alkenyl group having 2 to 20 carbon atoms, preferably 2 to 10 carbon atoms, and more preferably 2 to 6 carbon atoms.

[0130] X in the general formula (6) represents an alicyclic hydrocarbon group, and the number of carbon atoms constituting the alicyclic hydrocarbon group is usually 4 to 20, preferably 4 to 10, and more preferably 5 to 7. By setting the number of carbon atoms constituting the alicyclic structure within this range, birefringence can be reduced. In addition, the alicyclic structure is not limited to a monocyclic structure, and may be a polycyclic structure such as a norbornane ring or a bicyclohexane ring.

[0131] The alicyclic hydrocarbon group may have a carbon-carbon unsaturated bond, and its content is less than 10% of all carbon-carbon bonds, preferably less than 5%, and more preferably less than 3%. By setting the carbon-carbon unsaturated bonds of the alicyclic hydrocarbon group to within this range, transparency and heat resistance are improved. In addition, any of hydrogen atoms, hydrocarbon groups, halogen atoms, alkoxy groups, hydroxyl groups, ether groups, ester groups, cyano groups, amide groups, imide groups, silyl groups, and chain hydrocarbon groups substituted with polar groups (halogen atoms, alkoxy groups, hydroxyl groups, ether groups, ester groups, cyano groups, amide groups, imide groups, or silyl groups) may be bonded to the carbon constituting the alicyclic hydrocarbon group, wherein, from the viewpoint of heat resistance and low water absorption, hydrogen atoms or chain hydrocarbon groups having 1 to 6 carbon atoms are preferred.

[0132] Among the structural units represented by the general formula (6), the structural units represented by the following general formula (7) are preferred from the viewpoint of heat resistance and low water absorption.

[0133] Chemical formula 7

[0134]

[0135] In the general formula (7), Ra, Rb, Rc and Rd each independently represent a hydrogen atom or a lower chain hydrocarbon group, and a hydrogen atom or a lower alkyl group having 1 to 6 carbon atoms is preferred because of its excellent heat resistance and low water absorption.

[0136] The alicyclic vinyl structural units may be used alone or in combination of two or more.

[0137] The method for forming the heat-resistant acrylic resin containing an alicyclic vinyl structural unit is not particularly limited, and examples thereof include (1) a method of copolymerizing an aromatic vinyl compound with other monomers containing (meth)acrylic acid or (meth)acrylate, and hydrogenating the carbon-carbon unsaturated bonds of the main chain and the aromatic ring; (2) a method of copolymerizing an alicyclic vinyl compound with other monomers containing (meth)acrylic acid or (meth)acrylate, and hydrogenating as needed. The method (1) is preferred because it can more efficiently obtain an alicyclic hydrocarbon copolymer.

[0138] The aromatic vinyl compound used in the method of (1) above is not particularly limited. Examples thereof include styrene, α-methylstyrene, α-ethylstyrene, α-propylstyrene, α-isopropylstyrene, α-tert-butylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2,4-diisopropylstyrene, 2,4-dimethylstyrene, 4-tert-butylstyrene, 5-tert-butyl-2-methylstyrene, monochlorostyrene, dichlorostyrene, monofluorostyrene, 4-phenylstyrene, etc. Among them, styrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, etc. are preferred.

[0139] The alicyclic vinyl compound used in the method (2) above is not particularly limited, and examples thereof include cyclobutylethylene, cyclopentylethylene, cyclohexylethylene (vinylcyclohexane), cycloheptylethylene, cyclooctylethylene, norbornylethylene, dicyclohexylethylene, α-methylcyclohexylethylene, α-tert-butylcyclohexylethylene, cyclopentenylethylene, cyclohexenylethylene, cycloheptenylethylene, cyclooctenylethylene, cyclodecenylethylene, norbornylethylene, α-methylcyclohexenylethylene, and α-tert-butylcyclohexenylethylene. Among them, cyclohexylethylene (vinylcyclohexane) is preferred.

[0140] From the viewpoint of heat resistance, molding processability and optical properties, the content of the alicyclic vinyl structural unit is preferably 0 to 80% by mass, more preferably 2 to 60% by mass, and even more preferably 5 to 40% by mass based on 100% by mass of the heat-resistant acrylic resin.

[0141] [Method for producing heat-resistant acrylic resin]

[0142] The method for producing the heat-resistant acrylic resin is not particularly limited as long as the heat-resistant acrylic resin can be obtained, and a conventionally known method can be used. For example, the heat-resistant acrylic resin can be produced by using each monomer for forming each structural unit and utilizing bulk polymerization, solution polymerization, suspension polymerization, precipitation polymerization, or emulsion polymerization. In the production of the heat-resistant acrylic resin, bulk polymerization and solution polymerization are preferably used, and solution polymerization is more preferably used.

[0143] The heat-resistant acrylic resin may be produced in a continuous manner or in a batch manner.

[0144] In the method for producing the heat-resistant acrylic resin, it is preferred to polymerize the monomer by radical polymerization.

[0145] In the method for producing the heat-resistant acrylic resin, a known polymerization initiator, chain transfer agent, and the like may be used as necessary.

[0146] [additive]

[0147] The lens body P1 is not particularly limited as long as it can exhibit the effects of the present invention, and may contain various additives.

[0148] The additives are not particularly limited, and examples thereof include antioxidants, light stabilizers such as hindered amine light stabilizers, ultraviolet absorbers, mold release agents, lubricants, other thermoplastic resins, paraffin-based process oils, cycloparaffin-based process oils, aromatic process oils, paraffins, organopolysiloxanes, softeners / plasticizers such as mineral oils, flame retardants, antistatic agents, inorganic fillers such as organic fibers and pigments such as iron oxide, compatibilizers, dispersants, reinforcing agents such as glass fibers, carbon fibers, and metal whiskers, colorants, organic phosphorus compounds such as phosphites, phosphonites, and phosphates, other additives, or mixtures thereof.

[0149] The method for kneading the heat-resistant acrylic resin and the additive is not particularly limited, and for example, a method of kneading using a kneading machine such as an extruder, a heating roll, a kneader, a drum mixer, a Banbury mixer, etc. Among them, kneading using an extruder is preferred from the viewpoint of productivity. In order to reduce volatile matter, it is preferred to provide a vent in the extruder.

[0150] The kneading temperature can be set according to the preferred processing temperature of the heat-resistant acrylic resin or other thermoplastic resin added as an additive, and is 140 to 350°C as a reference, and preferably 180 to 300°C.

[0151] From the viewpoint of ease of molding and mechanical strength, the weight average molecular weight (Mw) of the resin composition containing the heat-resistant acrylic resin and any additives is preferably 10,000 to 1,000,000, more preferably 50,000 to 500,000, and further preferably 70,000 to 200,000. When the weight average molecular weight (Mw) is within the above range, there is a tendency that the balance between the molding processability and the mechanical strength of the lens body P1 becomes good.

[0152] In addition, for the resin composition containing a heat-resistant acrylic resin and any additives, from the viewpoint of ease of molding, mechanical strength, and solvent resistance, the molecular weight distribution (weight average molecular weight Mw / number average molecular weight Mn) is preferably 1.25 to 3.00, more preferably 1.50 to 2.75, and further preferably 1.75 to 2.50. When the molecular weight distribution (Mw / Mn) is within the above range, there is a tendency that the balance of molding processability, mechanical strength, and solvent resistance of the lens body P1 becomes good.

[0153] In addition, the weight average molecular weight (Mw) and the number average molecular weight (Mn) of the resin composition can be measured using gel permeation chromatography (GPC), and specifically, can be measured by the method described in Examples described later.

[0154] The lens body P1 is formed by molding a resin composition containing a heat-resistant acrylic resin and any additives. As a manufacturing method of the lens body P1, a molding method such as injection molding, compression molding, extrusion molding, blow molding, injection molding, etc. can be used. In addition, a desired shape can also be obtained by cutting from a resin block. Among them, injection molding is preferred from the viewpoint of productivity.

[0155] The injection molding method and the injection molding machine are not particularly limited, and conventionally known injection molding methods and injection molding machines can be used.

[0156] In general, the injection molding method consists of the following steps: (1) an injection step of melting the resin and filling the cavity of the mold at a controlled temperature with the molten resin; (2) a holding pressure step of applying pressure to the cavity until the gate is sealed and injecting a resin equivalent to the amount of the molten resin filled in the injection step that contacts the mold and contracts due to cooling; (3) a cooling step of releasing the holding pressure and holding the molded product until the resin is cooled; and (4) a step of opening the mold and taking out the cooled molded product.

[0157] At this time, the molding temperature is preferably in the range of Tg+100°C to Tg+180°C, and more preferably in the range of Tg+110°C to Tg+160°C, based on the glass transition temperature (Tg) of the resin composition. Here, the molding temperature refers to the barrel setting temperature of the injection molding machine. The higher the molding temperature, the better the shape transferability of the lens body P1 can be obtained. However, under high temperature conditions, coloring caused by thermal degradation during retention in the molding machine is promoted. Therefore, the molding temperature should be appropriately selected.

[0158] The mold temperature is preferably in the range of Tg-70°C to Tg, and more preferably in the range of Tg-50°C to Tg-10°C, based on the glass transition temperature (Tg) of the resin composition.

[0159] The injection speed can be appropriately selected according to the thickness and size of the lens body P1 to be obtained, and can be appropriately selected from the range of 2 to 1000 mm / sec, for example.

[0160] The pressure for holding the pressure can be appropriately selected according to the shape of the lens body P1 to be obtained, and can be appropriately selected within the range of 30 to 150 MPa, for example.

[0161] Here, the pressure for holding pressure refers to the pressure maintained by the screw for further sending out the molten resin from the gate after the molten resin is filled.

[0162] In order to relieve the residual stress generated by injection molding and reduce the phase difference of the lens body P1, an annealing process may be performed. Based on the glass transition temperature (Tg) of the resin composition, the annealing temperature is preferably in the range of Tg-50°C to Tg, and more preferably in the range of Tg-30°C to Tg-10°C.

[0163] <Base coating>

[0164] In the plastic lens P of this embodiment, the primer layer P2 is a layer covering the optically effective surface of at least one surface of the lens body P1. The primer layer P2 improves the adhesion between the lens body (plastic lens substrate) P1 and the anti-reflection layer P3, and suppresses the generation of cracks in the anti-reflection layer P3 under a high temperature environment or a high temperature and high humidity environment. Therefore, the plastic lens P of this embodiment becomes a lens with excellent durability.

[0165] The bottom coating P2 is made of silicon oxide SiO x As described later, for example, when SiO is used as a material for film formation by vacuum deposition, the composition of the undercoat layer P2 can be made into silicon oxide SiO by oxidizing the deposition material while forming the film in an oxygen environment. x (1<x<2).

[0166] Generally, when a film product in which an anti-reflection layer composed of a metal oxide is formed on a resin substrate, a wet heat test is performed. Due to the difference in linear expansion coefficient and water absorption between the resin substrate and the anti-reflection layer, the anti-reflection layer cannot follow the expansion of the resin substrate, and cracks are generated. However, the plastic lens P of this embodiment has a silicon oxide SiO2 between the lens body P1 and the anti-reflection layer P3. x The undercoat layer P2 having the structure of (1<x<2) serves as a buffer layer, thereby suppressing the occurrence of cracks.

[0167] The refractive index of the primer layer P2 at a wavelength of 500 nm is preferably 1.60 or more, more preferably 1.61 or more, and further preferably 1.62 or more. In addition, the refractive index of the primer layer P2 is preferably 1.70 or less, more preferably 1.68 or less, and further preferably 1.66 or less. When the refractive index is within this range, a high inhibitory effect is exerted on the generation of cracks after the wet heat test.

[0168] The refractive index of the undercoat layer P2 can be adjusted by adjusting the silicon oxide SiO x The composition of (1<x<2) is controlled. For example, when the base coating P2 is formed by vacuum evaporation described later, if the oxygen partial pressure is increased (increased oxygen introduction amount), the composition is close to SiO2 and the refractive index becomes lower. If the oxygen partial pressure is reduced (reduced oxygen introduction amount), the composition is close to SiO and the refractive index becomes higher.

[0169] In addition, the refractive index of the primer layer P2 can be measured by the method described in Examples mentioned later.

[0170] The thickness (film thickness) of the primer layer P2 is preferably greater than 300nm, more preferably greater than 305nm, further preferably greater than 310nm, further preferably greater than 315nm, and particularly preferably greater than 320nm. In addition, the thickness (film thickness) of the primer layer P2 is preferably less than 1000nm, more preferably less than 900nm, further preferably less than 800nm, further preferably less than 700nm, and particularly preferably less than 650nm. When the thickness (film thickness) of the primer layer P2 is within this range, as described later, when the anti-reflection layer P3 is formed by vacuum evaporation using an evaporation device having an electron beam heating type evaporation source, it is possible to prevent reflected electrons from reaching the surface of the lens body P1, thereby preventing the embrittlement of the lens body P1 caused by reflected electrons and the decrease in the adhesion with the anti-reflection layer P3 caused by the embrittlement of the lens body P1. In addition, the generation of cracks after the wet heat test can also be suppressed.

[0171] The thickness (film thickness) of the primer layer P2 can be determined, for example, by direct observation of a cross section using an electron microscope, ellipsometry, or spectral reflectance method. Specifically, it can be determined by the method described in the examples described below.

[0172] The undercoat layer P2 can be formed by vacuum deposition. In vacuum deposition, a deposition material is heated in a vacuum chamber to vaporize or sublime, and the material adheres to the surface of a substrate at a separate position in the chamber to form a thin film.

[0173] The evaporation device used in the vacuum evaporation method has a chamber and an evaporation source disposed in the chamber, and the substrate to be film-formed is held in the chamber. As the evaporation source, for example, a resistance heating type evaporation source or an electron beam heating type evaporation source is used. The schematic structure of a representative evaporation device is shown in Figure 2 . Figure 2 (a) is an example of a vapor deposition device having a resistance heating type vapor deposition source, Figure 2 (b) is an example of a vapor deposition device having an electron beam heating type vapor deposition source (electron gun). Although not shown in the figure, a vapor deposition device having both a resistance heating type vapor deposition source and an electron beam heating type vapor deposition source can also be used.

[0174] exist Figure 2 In the evaporation device 11 of (a), 12 is a chamber, 13 is a resistance heating power supply, 14 is a evaporation cover, 15 is a boat, and 16 is a baffle. It should be noted that the resistance heating power supply 13 and the boat 15 are collectively referred to as an evaporation source. When the boat 15 is heated by the resistance heating power supply 13, the evaporation material 17 is heated by the heat to generate steam. The generated steam reaches the film-forming object substrate 18 held in the evaporation cover 14 and accumulates, thereby forming a thin film 19 composed of the evaporation material 17. A plurality of boats 15 can be arranged in the evaporation device 11, thereby increasing the film thickness of the same evaporation material, or forming a film of a plurality of evaporation materials (not shown).

[0175] In addition, Figure 2In the evaporation device 20 of (b), 21 is a chamber, 22 is an electron gun, 23 is an electron gun power supply, 24 is an evaporation cover, 25 is a crucible, 26 is a pole piece, and 27 is a baffle. It should be noted that the electron gun power supply 23, the electron gun 22 and the crucible 25 are collectively referred to as an evaporation source. The electron beam 32 generated from the electron gun 22 is deflected by more than 150° (for example, 180°, 270°) in the forward direction under the action of the magnetic field formed by the pole piece 26, and irradiates the evaporation material 29 contained in the crucible 25. When the electron beam 32 is irradiated to the evaporation material 29, the evaporation material 29 is heated to generate vapor. The generated vapor reaches the film-forming target substrate 30 held in the evaporation cover 24 and accumulates, thereby forming a thin film 31 composed of the evaporation material 29. A plurality of crucibles 25 can be set on a rotating table, and by rotating the rotating table, any crucible can be arranged at the electron beam irradiation position (not shown).

[0176] As described above, when the electron beam 32 is incident on the evaporation material 29, a portion of the irradiated electrons are reflected (backscattered) on the surface of the evaporation material 29 due to the input power and material properties, so that a certain amount of reflected electrons 33 are scattered. When the reflected electrons 33 are repeatedly reflected on the inner wall of the evaporation device and reach the substrate 30, resin decomposition occurs (embrittlement of the substrate 30), causing poor adhesion between the substrate 30 and the film 31 (the film 31 is easily peeled off from the embrittled part of the substrate 30). Acrylic resin is a material that is particularly susceptible to the influence of the reflected electrons 33 compared to other resins. In order to obtain good adhesion, it is necessary to suppress the influence of the reflected electrons 33. As a device for capturing the reflected electrons 33, for example, a reflected electron trap has been proposed.

[0177] If a reflected electron trap is used, it is possible to prevent problems such as damage to the substrate and changes in the film quality of the thin film caused by the temperature rise of the substrate when the reflected electrons reach the substrate, and therefore it is preferred. As long as the reflected electron trap has the performance of fully capturing the reflected electrons, any reflected electron trap can be used. As examples, there can be cited a physical barrier type that attenuates the energy of the reflected electrons by causing the reflected electrons to collide multiple times inside the barrier in an opening provided at the landing point of the reflected electrons or in an L-shaped / U-shaped shape provided in the forward direction of the reflected electrons, and a magnetic field deflection type that deflects the forward direction of the reflected electrons using a magnetic field to capture the reflected electrons. In the case of using a reflected electron trap, since the performance of capturing reflected electrons is high, it is preferred to use a magnetic field deflection type, and it is further preferred to use a magnetic field deflection type and a physical barrier type in combination. Figure 2 The reflection electron trap 28 of (b) is an example of a magnetic field deflection type.

[0178] The general vacuum deposition process for optical thin films includes the following six steps.

[0179] (1) The substrate is fixed to the vapor deposition cover, and the vapor deposition cover is placed above the chamber. The chamber is evacuated to a high vacuum state.

[0180] (2) The substrate is heated together with the vapor deposition cover using a halogen heater, a jacket heater, etc. At this time, the vapor deposition cover is rotated while heating in order to perform heating uniformly.

[0181] (3) With the baffle closed, the deposition material is melted in (pre-melted). In the case of sublimable materials such as SiO2, since it can be sublimated in a granular state, strictly speaking, pre-melting is not required. From the perspective of smoothly transferring to the following step (4), pre-heating is preferably performed (hereinafter, melting in and pre-heating are collectively referred to as pre-melting). In the case of fusible materials such as Ti3O5, pre-melting is required to prevent sudden boiling (splashing) and stabilize the film formation rate. It should be noted that in the case of electron beam heating, during the pre-melting process, reflected electrons sometimes fly out from the gaps in the baffle, reach the substrate and have an adverse effect on the adhesion. Therefore, it is preferably performed in a short time.

[0182] (4) When the pressure in the chamber reaches a predetermined vacuum pressure (basic vacuum pressure) and the substrate temperature stabilizes, the shutter is opened to allow the atoms / molecules of the vapor deposition material that have become gas to accumulate on the substrate surface (evaporation).

[0183] (5) After a vapor-deposited thin film having a predetermined thickness is formed on the substrate, the shutter is closed to terminate the vapor deposition.

[0184] (6) The vacuum is broken, and the deposition cover and the substrate with the deposited thin film are taken out from the chamber.

[0185] For the above six steps, steps (1), (2), and (3) are usually performed simultaneously, and then steps (4), (5), and (6) are performed sequentially. It should be noted that heating the substrate in step (2) is optional and may not be performed.

[0186] In addition, when using different vapor deposition materials to form a multilayer film, steps (3) to (5) are repeatedly performed in the film formation of the second material and later to form the film (hereinafter, the film formation process of the vapor deposition material after the second material is recorded as (3)', (4)', (5)'). At this time, the pre-melting of the vapor deposition material after the second material (step (3)') can be carried out simultaneously with the pre-melting of the first material (step (3)). By performing step (3)' simultaneously with step (3), after the vapor deposition (step (4)) of the first material is completed, it is possible to immediately transfer to the vapor deposition (step (4)') of the second material. Therefore, it has the advantage of being able to efficiently perform vacuum vapor deposition of a multilayer film composed of multiple materials.

[0187] In step (4), it is generally known that an oxide film is formed by vapor deposition while introducing oxygen into the chamber and reacting it with atoms / molecules of the vapor deposition material, or a mixed film is formed by using a plurality of vapor deposition materials at the same time. In addition, ion beam assisted vapor deposition (IAD) is widely used, which increases the filling density of the film and improves the adhesion by irradiating the surface of the film being formed with ions, and ion plating is widely used, which increases the filling density of the film and improves the adhesion by passing vapor deposition particles in a gas through a plasma so that the vapor deposition particles have a positive charge, and negatively charges the substrate to attract the gas vapor deposition particles and deposit them, thereby increasing the filling density of the film and improving the adhesion.

[0188] In the film formation of the primer layer P2 of the present embodiment, in the vacuum evacuation of the chamber in step (1), the pressure in the chamber is preferably less than 2.0×10 -3 Pa method for vacuuming.

[0189] In heating the vapor deposition material in steps (3) and (4), a method such as resistance heating, electron beam, high frequency induction, laser, etc. can be appropriately selected according to the vapor deposition material, the type of substrate, and the target characteristics of the thin film to be produced. In the film formation of the primer layer P2 of this embodiment, SiO is used as the vapor deposition material, and as the heating method, from the viewpoint of preventing embrittlement of the lens body P1, a resistance heating method that does not generate reflected electrons is preferably used.

[0190] In the vapor deposition of step (4), oxygen can be introduced into the chamber to react with atoms / molecules of the vapor deposition material while film formation is performed. In the film formation of the primer layer P2 of this embodiment, it is preferred to control the amount of oxygen introduced so that the pressure in the chamber is less than 1.0×10 -2 Pa.

[0191] <Anti-reflection layer>

[0192] In the plastic lens P of this embodiment, the antireflection layer P3 is a layer covering the primer layer P2 from the side opposite to the lens body P1. That is, in the plastic lens P of this embodiment, the primer layer P2 and the antireflection layer P3 are sequentially stacked on the optically effective surface of the lens body P1.

[0193] The antireflection layer P3 has a function of preventing the surface of the plastic lens P from reflecting.

[0194] Preferably, the anti-reflection layer P3 is composed of a dielectric multilayer film formed by alternately stacking a high refractive index film and a low refractive index film, wherein the high refractive index film is composed of a high refractive index material, and the low refractive index film is composed of a low refractive index material having a refractive index lower than that of the high refractive index material. If the anti-reflection layer P3 is a dielectric multilayer film of the above-mentioned structure, the reflectivity can be reduced for light and light beams in a wide range of wavelength regions.

[0195] As the high refractive index material for forming the high refractive index film, known materials can be used, specifically, for example, titanium oxide, zirconium oxide, tantalum pentoxide, niobium pentoxide, zinc sulfide, cerium oxide, hafnium oxide, lanthanum titanate, antimony oxide, indium oxide, tin oxide, and mixtures thereof can be used. In addition, by using materials sold with low oxidation numbers such as Ti2O3 and Ti3O5, or metal materials as evaporation materials, while introducing oxygen into the chamber, evaporation can also be performed, thereby forming an oxide film into which any amount of oxygen is introduced. In the anti-reflection layer P3 of the present embodiment, it is preferred that the high refractive index film is composed of a high refractive index material including any one or more of titanium oxide and zirconium oxide. When the high refractive index film includes any one or more of titanium oxide and zirconium oxide, it is a preferred case from the viewpoint of adhesion with the lens body P1 and the primer layer P2, ease of material supply, film stability, and controllability of optical characteristics in the visible light region.

[0196] When the antireflection layer P3 includes a plurality of high refractive index films, the composition of each high refractive index film can be appropriately set according to the design of optical characteristics. Therefore, the composition of each high refractive index film may be the same or different.

[0197] The refractive index of each high refractive index film at a wavelength of 500 nm is preferably 1.80 or more, more preferably 1.90 or more, and further preferably 2.00 or more. In addition, the refractive index of each high refractive index film is preferably 2.50 or less, more preferably 2.45 or less, and further preferably 2.40 or less.

[0198] In addition, the refractive index of the high refractive index film can be measured by the method described in Examples mentioned later.

[0199] The thickness (film thickness) of each high refractive index film is preferably more than 6nm, more preferably more than 8nm, and more preferably more than 10nm. In addition, the thickness (film thickness) of each high refractive index film is preferably less than 150nm, more preferably less than 125nm, and more preferably less than 100nm. When the thickness (film thickness) of each high refractive index film is in this range, there is a tendency that the balance of film adhesion, damage resistance, and controllability of optical properties becomes good.

[0200] The thickness (film thickness) of the high refractive index film can be determined, for example, by direct observation of a cross section using an electron microscope, ellipsometry, or spectral reflectance method, and specifically, by the method described in the examples described below.

[0201] As the low refractive index material forming the low refractive index film, known materials can be used, specifically, for example, silicon oxide, magnesium fluoride, yttrium fluoride, chiolite, cryolite, aluminum oxide and their mixtures can be used. In addition, materials sold with low oxidation numbers such as SiO, metal materials, are used as evaporation materials, and oxygen is introduced into the chamber while evaporation is performed, so that an oxide film with any amount of oxygen introduced can also be formed. In the anti-reflection layer P3 of the present embodiment, it is preferred that the low refractive index film comprises silicon oxide (wherein, compared with the above-mentioned base coating layer P2, the refractive index under the condition of a wavelength of 500nm is low). When the low refractive index film comprises the above-mentioned silicon oxide, it is preferred from the viewpoint of the ease of material supply, the controllability of the degree of oxidation, and the stability of film formation. It should be noted that as a method for adjusting the refractive index of the low-refractive index film containing silicon oxide to be lower than the refractive index of the base coating layer P2, for example, there can be cited a method of using SiO2 as the vapor-deposition material of silicon oxide in the anti-reflection layer P3, and a method of adjusting the oxygen partial pressure (oxygen introduction amount) when the base coating layer P2 is formed by vacuum evaporation as described later. If the oxygen partial pressure is increased (the oxygen introduction amount is increased), the composition is close to SiO2 and the refractive index becomes lower. If the oxygen partial pressure is reduced (the oxygen introduction amount is reduced), the composition is close to SiO and the refractive index becomes higher.

[0202] When the antireflection layer P3 includes a plurality of low-refractive index films, the composition of each low-refractive index film can be appropriately set according to the design of optical characteristics. Therefore, the composition of each low-refractive index film may be the same or different.

[0203] The refractive index of each low refractive index film at a wavelength of 500 nm is preferably 1.10 or more, more preferably 1.20 or more, and further preferably 1.30 or more. In addition, the refractive index of each low refractive index film is preferably 1.70 or less, more preferably 1.60 or less, and further preferably 1.50 or less.

[0204] In addition, the refractive index of the low-refractive-index film can be measured by the method described in Examples described later.

[0205] The thickness (film thickness) of each low refractive index film is preferably more than 10nm, more preferably more than 15nm, and more preferably more than 20nm. In addition, the thickness (film thickness) of each low refractive index film is preferably less than 200nm, more preferably less than 175nm, and more preferably less than 150nm. When the thickness (film thickness) of each low refractive index film is in this range, there is a tendency that the balance of film adhesion, damage resistance, and controllability of optical characteristics becomes good.

[0206] The thickness (film thickness) of the low refractive index film can be determined, for example, by direct observation of a cross section using an electron microscope, ellipsometry, or spectral reflectance method, and specifically, by the method described in Examples below.

[0207] The total thickness (total film thickness) of the anti-reflection layer P3 is preferably 100 nm or more, more preferably 125 nm or more, and further preferably 150 nm or more. In addition, the total thickness (total film thickness) of the anti-reflection layer P3 is preferably 500 nm or less, more preferably 400 nm or less, and further preferably 300 nm or less. When the total thickness (total film thickness) of the anti-reflection layer P3 is within this range, there is a tendency that the adhesion of the anti-reflection layer P3 to the lens body P1 and the primer layer P2 becomes good.

[0208] The total thickness (total film thickness) of the antireflection layer P3 can be determined, for example, by direct observation of a cross section using an electron microscope, ellipsometry, or a spectral reflectance method. Specifically, it can be determined by the method described in the examples described below.

[0209] The anti-reflection layer P3 of this embodiment can be formed by vacuum evaporation in the same manner as the base coat layer P2. Generally, compared with the wet film forming method, the shape control of the dry film forming method such as the vacuum evaporation method is excellent. Therefore, for the plastic lens P of this embodiment, the base coat layer P2 and the anti-reflection layer P3 are formed by vacuum evaporation, thereby becoming a plastic lens with excellent shape accuracy that can also cope with applications that require high control of the surface shape. In addition, for the plastic lens P of this embodiment, since the base coat layer P2 and the anti-reflection layer P3 can be formed continuously by vacuum evaporation, the number of processes and operation time can be shortened, and the productivity is excellent.

[0210] In forming the antireflection layer P3 of the present embodiment, in heating the deposition material in the above-mentioned vacuum deposition steps (3) and (4), resistance heating or electron beams are preferably used as the heating method, and electron beams are particularly preferably used.

[0211] In the pre-melting of the vapor deposition material in steps (3) and (3)', from the perspective of operating efficiency, when resistance heating or an electron beam generated by an electron gun with a reflective electron trap is used as the heating method, when the above-mentioned base coat P2 is formed, the pre-melting of the vapor deposition material of the anti-reflection layer P3 can also be carried out simultaneously with the pre-melting of the vapor deposition material of the base coat P2.

[0212] In the vapor deposition step (4), it is preferred that the amount of oxygen introduced be controlled so that the pressure in the chamber becomes 1.0×10 -3 Pa~5.0×10 -2 The range of Pa.

[0213] <Items using plastic lenses>

[0214] The plastic lens of the present embodiment can be suitably used as a lens in household goods, OA equipment, AV equipment, battery and electrical equipment parts, lighting equipment, automobile parts, and the like.

[0215] As an example of preferred use, a lens for a VR (Virtual Reality) head mounted display (HMD) can be cited. A head mounted display is an image display device worn on the head, and therefore is required to be small, lightweight, and less uncomfortable to wear. As a method for miniaturization, a method has been proposed in which a 1 / 4 wavelength plate and a reflective polarizing plate are combined with a lens to change the polarization state of light after passing through the lens to switch between reflection and transmission, so that an image can be reciprocated one and a half times in one lens (U.S. Patent No. 6563638, Japanese Patent Publication No. 2017-21321, etc.).

[0216] The above method is based on the following principle, for example.

[0217] A quarter-wave plate and a reflective polarizing plate are arranged on the back side of a lens coated with a partial reflection coating on the front surface, and light incident from the front surface of the lens as circularly polarized light is converted into linearly polarized light by the quarter-wave plate after passing through the lens. The linearly polarized light is reflected by the reflective polarizing plate, and is converted into circularly polarized light opposite to the original light by the quarter-wave plate again, and enters the lens from the back side, reaching the partially reflection coating portion of the front surface. The light emitted from the back side of the lens after being reflected by the partially reflection coating portion is converted into linearly polarized light 90° different from the original direction by the quarter-wave plate, and passes through the reflective polarizing plate, and enters the eye as an image. In the manner described above, a high magnification and a wide field of view can be obtained even in a thin optical module.

[0218] If the polarization state changes during the process of passing through the lens, for example, a portion of the light will pass through the reflective polarizer after passing through the lens for the first time, and the image with low magnification overlaps with the image with high magnification, making it difficult to obtain a clear image. Therefore, a lens with low birefringence is required. In addition, since the influence of humidity changes during use on the imaging properties accompanied by the shape change of the lens is also unfavorable, a lens with low hygroscopicity and high shape stability in a high temperature and high humidity environment is required. In this regard, the plastic lens of this embodiment has excellent shape accuracy and extremely good durability, so it is preferred.

[0219] In addition, as other examples of preferably using the plastic lens of the present embodiment, lenses for household items, OA equipment, AV equipment, battery electrical equipment parts, lighting equipment, etc., for example, lenses for smartphone cameras, tablet cameras, lenses used in telephoto cameras (periscope cameras) of folded optical systems (folded optics); lenses used in VR (Virtual Reality) / AR (Augmented Reality) / MR (Mixed Reality) / SR (Substitutional Reality) / DR (Diminished Reality) / XR (Cross Reality) head-mounted displays, liquid crystal projectors, near-infrared sensors (LiDAR; Light Detection and Ranging), etc., especially small thin-walled optical lenses with uneven shapes; lenses for optical communications; lenses, Fresnel lenses, phase plates with microlens arrays, etc.

[0220] Examples of lenses used in automobile parts include lenses used in head-up displays, vehicle-mounted camera lenses (particularly, front lenses), and the like.

[0221] In addition, lenses used in floating displays can be cited, for example, retroreflective sheets, substrates of partially transparent mirrors, microlens arrays for constituting dihedral corner reflector arrays, lenses for magnifying or reducing images or correcting image planes or aberrations, etc.

[0222] Example

[0223] The present invention will be described in detail below with reference to Examples and Comparative Examples. However, the present invention is not limited to the following Examples.

[0224] The measurement and evaluation methods of the heat-resistant acrylic resins prepared in the Production Examples are as follows.

[0225] [Analysis of structural units]

[0226] Unless otherwise stated, 1 H-NMR determination and 13 The structural units of the heat-resistant acrylic resin produced in the production examples were identified by C-NMR measurement, and the amount thereof was calculated. 1 H-NMR determination and 13 The measurement conditions of C-NMR measurement are as follows.

[0227] Measuring equipment: ECZ400 manufactured by JEOL Ltd.

[0228] Determination solvent: CDCl3 or DMSO-d6.

[0229] Measurement temperature: 40℃.

[0230] [Determination of molecular weight]

[0231] The weight average molecular weight (Mw) and number average molecular weight (Mn) of the heat-resistant acrylic resin produced in the production examples were measured using the following apparatus and conditions.

[0232] Measuring apparatus: manufactured by Tosoh Corporation, gel permeation chromatography (HLC-8320GPC).

[0233] The measurement conditions are as follows.

[0234] Chromatographic columns: One TSK guard column SuperH-H, two TSKgel SuperHM-Ms, and one TSKgelSuperH2500 were connected in series in this order for use.

[0235] Column temperature: 40°C.

[0236] The developing solvent was tetrahydrofuran, and the flow rate was 0.6 mL / min. As an internal standard, 0.1 g / L of 2,6-di-tert-butyl-4-methylphenol (BHT) was added.

[0237] Detector: RI (differential refractometer) detector.

[0238] Detection sensitivity: 3.0mV / min.

[0239] Sample: 20 mL tetrahydrofuran solution of 0.02 g of heat-resistant acrylic resin.

[0240] Injection volume: 10 μL.

[0241] As standard samples for calibration curve, the following 10 types of polymethyl methacrylates having different molecular weights and known monodisperse weight peak molecular weights (manufactured by Polymer Laboratories; PMMA Calibration Kit MM-10) were used.

[0242] Weight peak molecular weight (Mp) Standard reagent 1 1916000 Standard reagent 2 625500 Standard reagent 3 298900 Standard reagent 4 138600 Standard reagent 5 60150 Standard reagent 6 27600 Standard reagent 7 10290 Standard reagent 8 5000 Standard reagent 9 2810 Standard reagent 10 850

[0243] Under the above conditions, the RI detection intensity with respect to the elution time of the heat-resistant acrylic resin was measured.

[0244] The weight average molecular weight (Mw) and number average molecular weight (Mn) of the heat-resistant acrylic resin are determined based on the calibration curve obtained by measuring the standard sample for the calibration curve, and the molecular weight distribution (Mw / Mn) is determined using these values.

[0245] [Determination of glass transition temperature]

[0246] The glass transition temperature (Tg) (° C.) of the heat-resistant acrylic resin was measured in accordance with JIS-K7121.

[0247] First, the sample was conditioned under a standard condition (23° C., 50% RH) (left at 23° C. for one week), and about 10 mg of the sample was cut out at four points (four places) to prepare test pieces.

[0248] Then, a differential scanning calorimeter (Diamond DSC manufactured by Perkin Elmer Japan) was used under the condition of a nitrogen flow rate of 25 mL / min. Here, the temperature was raised from room temperature (23°C) to 200°C at 10°C / min (primary heating), and maintained at 200°C for 5 minutes. After the sample was completely melted, the temperature was lowered from 200°C to 40°C at 10°C / min, and maintained at 40°C for 5 minutes. Further, a DSC curve was drawn during the period of heating again (secondary heating) under the above-mentioned heating conditions. In the DSC curve, the intersection of the step-shaped change part curve during the secondary heating and the straight line with the same distance from each baseline extension line in the vertical axis direction (midpoint glass transition temperature) was measured as the glass transition temperature (Tg) (°C). Four points were measured for each sample, and the arithmetic average (rounded off below the decimal point) of the four points was taken as the measured value.

[0249] [Determination of Vicat softening temperature]

[0250] The acrylic resin was placed in an injection molding machine (EC-100SX manufactured by Shibaura Machine Co., Ltd.) and a 1A dumbbell-shaped test piece was molded according to ISO8257-2. The test piece was conditioned in an oven at a specified temperature for 16 hours, then cooled in a desiccator at 23°C for 1 hour, and the Vicat softening temperature (°C) of the acrylic resin was measured according to ISO 306B50.

[0251] The raw materials used in the production examples are as follows.

[0252] [monomer]

[0253] Methyl methacrylate (MMA): manufactured by Asahi Kasei Co., Ltd.

[0254] N-Phenylmaleimide (phMI): manufactured by Nippon Shokubai Co., Ltd.

[0255] N-Cyclohexylmaleimide (chMI): manufactured by Nippon Shokubai Co., Ltd.

[0256] 2-(Hydroxymethyl)methyl acrylate (RHMA): manufactured by Combi-Blocks.

[0257] Styrene (St): manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.

[0258] [Organic solvents]

[0259] Meta-xylene (mXy): manufactured by Mitsubishi Gas Chemical Co., Ltd.

[0260] Toluene: manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.

[0261] Methyl isobutyrate: manufactured by Kanto Chemical Co., Ltd.

[0262] [Polymerization initiator]

[0263] 1,1-Di(tert-butylperoxy)cyclohexane: manufactured by NOF Corporation, Perhexa C.

[0264] Tert-amyl peroxyisononanoate: Luperox 570 manufactured by Arkema Yoshitomi, Ltd.

[0265] Tert-amyl peroxy 2-ethylhexanoate: Luperox 575 manufactured by Arkema Yoshitomi, Ltd.

[0266] [Chain transfer agent]

[0267] n-Octylmercaptan: manufactured by Chevron Phillips Chemical International Ltd.

[0268] [Other additives, etc.]

[0269] Stearyl phosphate: manufactured by Sakai Chemical Industry Co., Ltd., Phoslex A-18.

[0270] Monomethylamine: manufactured by Mitsubishi Gas Chemical Corporation.

[0271] Dimethyl carbonate: manufactured by FUJIFILM Wako Pure Chemical Corporation.

[0272] Triethylamine: manufactured by FUJIFILM Wako Pure Chemical Corporation.

[0273] Pd / C: Made by NECHEMCAT CORPORATION.

[0274] Rikemal H-100: manufactured by Riken Vitamin Co., Ltd.

[0275] (Production Example 1: Heat-resistant acrylic resin A)

[0276] 358.6 kg of methyl methacrylate (hereinafter referred to as MMA), 29.4 kg of N-phenylmaleimide (hereinafter referred to as phMI), 67.7 kg of N-cyclohexylmaleimide (hereinafter referred to as chMI), 0.77 kg of n-octyl mercaptan as a chain transfer agent, and 224.3 kg of meta-xylene (hereinafter referred to as mXy) ​​were weighed and added to a 1.25 m3 / 450 ft. warm oven equipped with a jacketed temperature control device and a stirring blade. 3 The mixture was stirred in the reactor to obtain a mixed monomer solution.

[0277] Then, 88.0 kg of MMA, 6.3 kg of phMI, and 142.4 kg of mXy were weighed and added to the tank 1, and stirred to obtain a mixed monomer solution for replenishment.

[0278] The internal liquid of the reactor was bubbled with nitrogen at a rate of 30 L / min for 1 hour, and nitrogen was bubbled with nitrogen at a rate of 10 L / min for 30 minutes into the tank 1 to remove dissolved oxygen.

[0279] Then, steam was blown into the jacket to raise the temperature of the solution in the reactor to 115°C, and a polymerization initiator solution prepared by dissolving 0.470 kg of 1,1-di(tert-butylperoxy)cyclohexane in 1.905 kg of mXy was added at a rate of 1.0 kg / hour while stirring at 50 rpm to start polymerization.

[0280] During the polymerization, the temperature of the solution in the reactor was controlled to 115±2° C. by temperature regulation using the jacket. 30 minutes after the start of the polymerization, the addition rate of the initiator solution was reduced to 0.5 kg / hour.

[0281] Furthermore, one hour after the start of the polymerization, all the mixed monomer solution for replenishment was added from the tank 1 at a constant rate over 4 hours.

[0282] Furthermore, the addition rate of the initiator solution was reduced to 0.25 kg / hour 3.5 hours after the start of the polymerization, and the addition was stopped 5 hours after the start of the polymerization.

[0283] After 12 hours had passed from the start of the polymerization, a polymer solution containing a heat-resistant acrylic resin having a ring structure in its structure (main chain) was obtained, and the polymerization was completed.

[0284] The polymer solution was supplied to a concentrator consisting of a tubular heat exchanger and a vaporizer preheated to 250°C for devolatilization. The vacuum degree of the vaporizer was 10 to 15 Torr. The resin flowing down from the vaporizer was discharged by a gear pump, extruded from a wire drawing die, water-cooled, and pelletized to obtain a heat-resistant acrylic resin A.

[0285] The composition of the obtained particles was confirmed, and the results showed that the structural units derived from the monomers MMA, phMI, and chMI in the copolymer were 81.0 mass%, 6.6 mass%, and 12.4 mass%, respectively. In addition, the weight average molecular weight was 108,000, Mw / Mn was 2.04, the glass transition temperature was 134°C, and the Vicat softening temperature was 124°C.

[0286] (Production Example 2: Heat-resistant acrylic resin B)

[0287] As the raw material resin, a methyl methacrylate-styrene copolymer (styrene content 8% by mass) with a molecular weight of 100,000 was used, and as the imidizing agent, monomethylamine was used. A meshing co-rotating twin-screw extruder with a diameter of 15 mm was used to produce a glutarimidized resin. The set temperature of each temperature control zone was set to 230-250°C, and the screw speed was set to 150 rpm. Methyl methacrylate-styrene copolymer (hereinafter also referred to as "MS resin") was supplied at 2 kg / hour, and after the resin was melted and filled by a kneading block, 8 parts by mass of monomethylamine relative to the resin was injected from a nozzle. A reverse screw was inserted at the end of the reaction zone to fill it with resin. The pressure at the exhaust port was reduced to -0.092 MPa to remove the by-products and excess monomethylamine after the reaction. The resin coming out in strands from the die head set at the outlet of the extruder was cooled in a water tank and granulated in a granulator to obtain a glutarimidized MS resin intermediate (1).

[0288] Then, for an intermeshing co-rotating twin-screw extruder with a diameter of 15 mm, the set temperature of each temperature control zone of the extruder was set to 230°C, the screw speed was set to 150 rpm, and the obtained glutarimidized MS resin intermediate (1) was supplied from the hopper at 1 kg / hour. After the resin was melted and filled by the kneading block, a mixed solution of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine relative to the resin was injected from the nozzle to reduce the carboxyl group in the resin. A reverse screw was placed at the end of the reaction zone to fill the resin. The pressure at the exhaust port was reduced to -0.092 MPa to remove the by-products and excess dimethyl carbonate after the reaction. The resin coming out in strands from the die head set at the outlet of the extruder was cooled by a water tank and granulated by a granulator to obtain a glutarimidized MS resin intermediate (2).

[0289] Furthermore, the glutarimidized MS resin intermediate (2) was fed into an intermeshing co-rotating twin-screw extruder having a diameter of 15 mm, under the conditions that the set temperature of each temperature control zone of the extruder was 230° C., the screw speed was 150 rpm, and the supply amount was 1 kg / hour. The pressure at the exhaust port was reduced to -0.095 MPa to remove the volatile parts such as unreacted by-products again. The devolatilized imide resin coming out of the die head provided at the outlet of the extruder in the form of strands was cooled in a water tank and pelletized in a pelletizer to obtain a heat-resistant acrylic resin B (glutarimidized MS resin).

[0290] The weight average molecular weight of the heat-resistant acrylic resin B is 85,000, and Mw / Mn is 1.8. The content of the monomer units in the copolymer is 8% by mass of styrene unit, 82% by mass of MMA unit, and 10% by mass of glutarimide unit. The glass transition temperature is 128°C and the Vicat softening temperature is 120°C.

[0291] (Production Example 3: Heat-resistant acrylic resin C)

[0292] 5.40 parts by mass of methyl 2-(hydroxymethyl)acrylate (hereinafter referred to as RHMA), 37.6 parts by mass of methyl methacrylate (hereinafter referred to as MMA), 0.450 parts by mass of styrene (hereinafter referred to as St), and 90.0 parts by mass of toluene were placed in a reaction container equipped with a stirring device, a temperature sensor, a cooling tube, a nitrogen introduction tube, and a dropping pump, and the temperature was raised to 105° C. while nitrogen was introduced.

[0293] As an initial initiator, a solution consisting of 3.63 parts by mass of toluene and 0.245 parts by mass of tert-amyl peroxyisononanoate was dripped over 9 minutes while solution polymerization was carried out at 105° C. to 110° C. Then, 11 minutes later, a solution consisting of 4.42 parts by mass of toluene and 0.298 parts by mass of tert-amyl peroxyisononanoate was dripped over 180 minutes as a dripping initiator. In addition, while the dripping initiator was added, a solution consisting of 6.6 parts by mass of RHMA, 45.9 parts by mass of MMA and 4.05 parts by mass of St was dripped over 180 minutes while solution polymerization was carried out at 105° C. to 110° C., and aging was carried out for 100 minutes.

[0294] To the obtained polymerization solution, a solution consisting of 1.20 parts by mass of toluene and 0.0750 parts by mass of stearyl phosphate as a catalyst for the cyclization condensation reaction (cyclization catalyst) was added, and a cyclization condensation reaction for forming a lactone ring structure was carried out under reflux at about 90° C. to 110° C. for 1.5 hours.

[0295] Then, the obtained polymer solution was passed through a multi-tube heat exchanger maintained at 220°C to complete the cyclization condensation reaction, and then introduced into a venting type screw twin-screw extruder (L / D=52) equipped with a blade disk type polymer filter (filtration accuracy 5μm) at the front end at a processing rate of 90 mass parts / hour in terms of resin amount, and the polymer solution was devolatilized. The venting type screw twin-screw extruder used had one rear vent and four front vents (called the first vent, the second vent, the third vent, and the fourth vent from the upstream side), the barrel temperature was 220°C, and the degree of decompression was set to 13.3 to 400hPa (10 to 300mmHg). During the devolatilization, ion exchange water was added from the rear of the first vent, the second vent, and the third vent at an introduction rate of 1.3 mass parts / hour.

[0296] The obtained heat-resistant acrylic resin C has a weight average molecular weight of 102,000, Mw / Mn of 2.3, a glass transition temperature of 125°C, a Vicat softening temperature of 116°C, and the proportions of MMA units, styrene units, lactone ring structures, and RHMA units in the copolymer are 76.8 mass%, 4.6 mass%, 16.9 mass%, and 1.7 mass%, respectively.

[0297] (Production Example 4: Heat-resistant acrylic resin D)

[0298] A monomer composition consisting of 75.09 parts by mass of MMA, 26.04 parts by mass of styrene, and 0.46 parts by mass of tert-amyl peroxy 2-ethylhexanoate as a polymerization initiator was continuously supplied at 1 kg / hour to a 10L complete mixing tank equipped with a helical ribbon impeller, and continuous polymerization was carried out at an average residence time of 2.5 hours and a polymerization temperature of 150°C. The liquid was continuously drawn out from the bottom to a predetermined level in the polymerization tank, and supplied to a concentrator consisting of a tubular heat exchanger and a vaporizer tank for devolatilization. The vacuum degree of the vaporizer tank was 10 to 15 Torr. The resin flowing down from the vaporizer tank was discharged by a screw pump, extruded from a wire drawing die, water-cooled, pelletized, and introduced into a desolventizing device to obtain a pelletized methyl methacrylate-styrene copolymer.

[0299] The copolymer was dissolved in methyl isobutyrate to prepare a 10% by mass methyl isobutyrate solution. 500 parts by mass of the 10% by mass methyl isobutyrate solution of the copolymer and 1 part by mass of 10% by mass Pd / C as a hydrogenation catalyst were added to a 1000 mL autoclave apparatus, and the mixture was kept at a hydrogen pressure of 9 MPa and 200° C. for 15 hours to hydrogenate the aromatic double bonds of the styrene portion of the copolymer. The hydrogenation catalyst was removed by a filter, 0.04 parts by mass of Rikemal H-100 was added to the polymer solution and mixed, and then supplied to a concentrator consisting of a tubular heat exchanger and a vaporizer tank for devolatilization. The vacuum degree of the vaporizer tank was 10 to 15 Torr. The resin flowing down from the vaporizer tank was discharged with a gear pump, extruded from a wire drawing die, and pelletized after water cooling to obtain a heat-resistant acrylic resin D.

[0300] The composition of the obtained pellets was confirmed, and the results showed that the structural units derived from MMA and vinylcyclohexane monomers in the copolymer were 73.2% by mass and 26.8% by mass, respectively. In addition, the weight average molecular weight was 148,000, Mw / Mn was 2.0, the glass transition temperature was 118°C, and the Vicat softening temperature was 112°C.

[0301] The measurement and evaluation methods of each layer formed in the examples and comparative examples are as follows.

[0302] [Refractive index]

[0303] A single layer was formed on a glass substrate (optical glass B270i) under the same film-forming conditions in advance, and the spectral reflectance was measured using an ultraviolet-visible-near-infrared spectrophotometer (manufactured by Hitachi High-Technologies Corporation, UH4150). Then, the refractive index of each layer formed in the examples and comparative examples at a wavelength of 500 nm was determined by the spectral reflectance method.

[0304] [Thickness of each layer (film thickness)]

[0305] The thickness (film thickness) of each layer formed in the examples and comparative examples was determined using a spectroscopic ellipsometer (UVISEL2, manufactured by Horiba, Ltd.). It should be noted that the film thickness was calculated using data of a sample formed in advance as a single layer on a glass substrate (optical glass B270i) under the same film forming conditions.

[0306] [Example 1]

[0307] (Lens molding)

[0308] The heat-resistant acrylic resin A obtained in Manufacturing Example 1 was injection molded using an injection molding machine (manufactured by FANUC CORPORATION, S-2000i50B) to obtain a plano-convex lens molded product (lens body) having an optical axis thickness of 3.2 mm and an effective diameter of φ41 mm. As a finished product, one surface of the surface including the optical axis was an aspherical surface with a curvature radius of R93.5 mm, and the cone constant k was -1.12452, with no even-numbered constants set. In addition, another surface of the surface including the optical axis was a planar surface with a curvature radius of ∞.

[0309] The barrel temperature was set to Tg of the heat-resistant acrylic resin A used + 135°C, and the mold temperature was set to Tg of the heat-resistant acrylic resin A used - 15°C. The holding pressure was set at 60 MPa for 4 seconds in the first stage, and then at 40 MPa for 3 seconds in the second stage to ease the stress and strain inside the molded product. In addition, the injection speed was set to 10 mm / s.

[0310] (Film formation of primer layer and anti-reflection layer)

[0311] On the flat surface side of the lens molded product, a primer layer and an antireflection layer were formed by vacuum deposition using a vacuum deposition apparatus (SAPIOSGC-1300 manufactured by Showa Vacuum Co., Ltd.).

[0312] The lens molded product is placed in the vacuum deposition device, and the vacuum chamber is evacuated to 1.5×10 -3 Pa. Then, the SiO particles filled in the molybdenum boat were heated by resistance heating to sublime, and the primer layer was formed in a manner that the film thickness was 320 nm. It should be noted that during the film formation, oxygen was introduced as a reaction gas to make the total pressure 1.8×10 - 3 Pa, the film formation object (lens molded product) is particularly formed without heating. In addition, before and during the film formation of the primer layer, the vapor deposition material used for the film formation of the antireflection layer in the subsequent process is not pre-melted.

[0313] Then, the Ti3O5 particles filled in the copper liner were heated by an electron gun to melt and vaporize them, and a TiO2 layer as a high refractive index layer was formed by electron beam evaporation. It should be noted that during the film formation, oxygen was introduced as a reaction gas to a total pressure of 1.3×10 -2 Pa, the film forming object (lens molding + primer) was formed without heating. In addition, the electron beam heating of Ti3O5 as the evaporation material was started with the shutter closed, and the evaporation material was pre-melted and the shutter was opened to form the film.

[0314] Then, the SiO2 particles filled in the copper liner were heated with an electron gun to sublime, and the SiO2 layer as a low refractive index layer was formed by electron beam evaporation. It should be noted that during the film formation, oxygen was introduced as a reaction gas to make the total pressure 1.3×10 -2 Pa, the film forming object (lens molding + primer + TiO2 layer) was formed without heating. In addition, the electron beam heating of SiO2 as the evaporation material was started with the shutter closed, and the shutter was opened after the evaporation material was pre-melted to form the film.

[0315] The film formation of the TiO2 layer and the SiO2 layer was repeated three times alternately, and the anti-reflection film of the structure shown in Table 1 was formed to obtain a plastic lens. It should be noted that the electron gun used for heating the vapor deposition material does not have a reflection electron trap. In addition, before and during the film formation of the TiO2 layer, the vapor deposition material used in the film formation of the SiO2 layer in the subsequent process is not pre-melted. Similarly, before and during the film formation of the SiO2 layer, the vapor deposition material used in the film formation of the TiO2 layer in the subsequent process is not pre-melted.

[0316] [Example 2]

[0317] A plastic lens including a primer layer and an antireflection layer was prepared in the same manner as in Example 1 except that the heat-resistant acrylic resin B was used instead of the heat-resistant acrylic resin A.

[0318] [Example 3]

[0319] A plastic lens including a primer layer and an antireflection layer was prepared in the same manner as in Example 1 except that the heat-resistant acrylic resin C was used instead of the heat-resistant acrylic resin A as the heat-resistant acrylic resin.

[0320] [Example 4]

[0321] A plastic lens including a primer layer and an antireflection layer was prepared in the same manner as in Example 1 except that the heat-resistant acrylic resin D was used instead of the heat-resistant acrylic resin A as the heat-resistant acrylic resin.

[0322] [Example 5]

[0323] A plastic lens including a primer layer and an antireflection layer was produced in the same manner as in Example 1 except that the primer layer was formed to have a film thickness of 450 nm.

[0324] [Example 6]

[0325] A plastic lens including a primer layer and an antireflection layer was produced in the same manner as in Example 1 except that the primer layer was formed to have a film thickness of 610 nm.

[0326] [Example 7]

[0327] A plastic lens including a primer layer and an antireflection layer was produced in the same manner as in Example 1 except that the primer layer was formed to have a film thickness of 900 nm.

[0328] [Example 8]

[0329] A plastic lens including a primer layer and an antireflection layer was produced in the same manner as in Example 1 except that an electron gun with a reflection electron trap was used as an electron gun for heating the vapor deposition material.

[0330] [Example 9]

[0331] A plastic lens having a primer layer and an anti-reflection layer was produced in the same manner as in Example 1, except that an electron gun with a reflection electron trap was used as an electron gun for heating the vapor deposition material, and pre-melting of the vapor deposition material used in the formation of the anti-reflection layer in the subsequent process was performed before and during the formation of the primer layer.

[0332] [Comparative Example 1]

[0333] When the primer layer is formed, oxygen is introduced so that the total pressure becomes 1.4×10 -2 A plastic lens including a primer layer and an antireflection layer was produced in the same manner as in Example 1 except for the above.

[0334] [Comparative Example 2]

[0335] A plastic lens including a primer layer and an antireflection layer was produced in the same manner as in Example 1 except that the primer layer was formed to a film thickness of 250 nm.

[0336] [Comparative Example 3]

[0337] A plastic lens including a primer layer and an antireflection layer was produced in the same manner as in Example 1 except that the primer layer was formed to a film thickness of 100 nm.

[0338] [Comparative Example 4]

[0339] A plastic lens having a primer layer and an antireflection layer was produced in the same manner as in Example 1 except that the primer layer was formed to a thickness of 100 nm and an electron gun with a reflection electron trap was used as an electron gun for heating the vapor deposition material.

[0340] [Comparative Example 5]

[0341] A plastic lens having a primer layer and an antireflection layer was prepared in the same manner as in Example 1 except that an acrylic resin having no heat resistance (DELPET 80N manufactured by Asahi Kasei Corporation, Vicat softening temperature 109° C.) was used instead of the heat-resistant acrylic resin A.

[0342] The measurement and evaluation methods of the plastic lenses produced in Examples and Comparative Examples are as follows.

[0343] (Durability Evaluation)

[0344] (1) Initial adhesion

[0345] In order to evaluate the coating adhesion of the plastic lens obtained by the examples and comparative examples, a cross-cut test was performed according to JIS K5600-5-6. A multi-blade cutting tool was used to make 25 1 mm × 1 mm squares on the flat side of the plastic lens, and a transparent tape ("LP-24" manufactured by NICHIBAN CO., LTD.) was pasted on the squares. After the tape was peeled off at once, the surface state of the cross-cut part was observed to see whether the film (primer coating and anti-reflection layer) peeled off. The results were classified as follows: Classification 0 or 1 was set as A (good), Classification 2 was set as B (practical), and Classifications 3 to 5 were set as C (poor).

[0346] (Classification)

[0347] 0: The edges of the cut are completely smooth, and there is no peeling on the squares.

[0348] 1: There is slight peeling of the film at the intersection of the cuts. When the area of ​​the entire cross-cut portion is set to 100%, the ratio of peeling in the cross-cut portion is not significantly greater than 5%.

[0349] 2: The film is slightly peeled along the edge of the cut and / or at the intersection. The entire area of ​​the cross-cut portion is set to 100%, and the ratio of peeling in the cross-cut portion is significantly greater than 5%, but not greater than 15%.

[0350] 3: The film peels off partially or completely along the edge of the cut and / or partially or completely in several squares. When the area of ​​the entire cross-cut portion is set as 100%, the proportion of peeling in the cross-cut portion is significantly greater than 15%, but not greater than 35%.

[0351] 4: The film peels off partially or completely along the edge of the cut, and / or peels off partially or completely in several squares. When the area of ​​the entire cross-cut portion is set as 100%, the percentage of peeling in the cross-cut portion is significantly greater than 35%, but not greater than 65%.

[0352] 5: Any case of peeling degree that cannot be classified even in category 4.

[0353] (2) Wet heat test

[0354] The wet heat test was carried out using the plastic lenses obtained in the examples and comparative examples. The plastic lenses were placed in a thermostat (PL-4KP manufactured by ESPEC CORP) set at 85°C and 85%RH and kept at 85°C and 85%RH for 200 hours. Then, the plastic lenses were taken out of the thermostat and kept in a thermostatic chamber at 23°C and 50%RH for 24 hours.

[0355] (2-1) Appearance changes after humidity and heat test

[0356] After the wet heat test, the plastic lens surface was visually observed to determine whether cracks were generated.

[0357] (2-2) Adhesion after humidity and heat test

[0358] For the plastic lens after the wet heat test, the adhesion of the films (primer layer and antireflection layer) was evaluated by the same evaluation method as that for the initial adhesion in (1).

[0359] Table 1 shows the results of each measurement and evaluation.

[0360]

[0361] The plastic lens of the present invention has excellent productivity and extremely good durability. Therefore, the plastic lens of the present invention can be used in applications such as lenses in household goods, OA equipment, AV equipment, battery and electrical equipment parts, lighting equipment, and automobile parts.

[0362] Lenses used in household items, OA equipment, AV equipment, battery electrical equipment parts, lighting equipment, etc., for example, include lenses for smartphone cameras or tablet cameras; lenses used in telephoto cameras (periscope cameras) of folded optics; lenses used in VR (virtual reality) / AR (augmented reality) / MR (mixed reality) / SR (alternative reality) / DR (de-reality) / XR (cross reality) head-mounted displays, liquid crystal projectors, near-infrared sensors (LiDAR), etc., especially small, thin-walled, non-uniformly shaped optical lenses; lenses for optical communications; lenses, Fresnel lenses, phase plates with microlens arrays, etc.

[0363] Examples of lenses used in automobile parts include lenses used in head-up displays, vehicle-mounted camera lenses (particularly, front lenses), and the like.

[0364] In addition, lenses used in floating displays can be cited, for example, retroreflective sheets, substrates of partially transparent mirrors, microlens arrays for constituting dihedral corner reflector arrays, lenses for magnifying or reducing images or correcting image planes or aberrations, etc.

Claims

1. A plastic lens comprising a lens body, a primer coating covering an optically effective surface of at least one surface of the lens body, and an antireflection layer covering the primer coating from a side opposite to the lens body, wherein: The lens body comprises a heat-resistant acrylic resin, The bottom coating is made of silicon oxide SiO x Composition, 1<x<2, The refractive index of the primer layer at a wavelength of 500 nm is 1.60 or more and 1.70 or less, The thickness of the primer layer is greater than 300 nm and less than 1000 nm.

2. The plastic lens according to claim 1, wherein: The thickness of the primer layer is greater than 300 nm and less than 800 nm.

3. The plastic lens according to claim 1 or 2, wherein: The antireflection layer is a layer formed by alternately stacking high refractive index films and low refractive index films, wherein the high refractive index films are made of a high refractive index material and the low refractive index films are made of a low refractive index material. The high refractive index material is any one or more of titanium oxide and zirconium oxide. The low refractive index material is silicon oxide having a refractive index lower than that of the undercoat layer at a wavelength of 500 nm.

4. The plastic lens according to claim 1 or 2, wherein: The heat-resistant acrylic resin has a glass transition temperature of 116° C. or higher.

5. The plastic lens according to claim 1 or 2, wherein: The heat-resistant acrylic resin contains a structural unit having a ring structure in its structure. The structural unit having a ring structure includes one or more selected from the group consisting of a cyclic imide structural unit, an aromatic vinyl structural unit, an alicyclic vinyl structural unit, and a lactone ring structural unit, The ratio of the structural unit having a ring structure in the heat-resistant acrylic resin is 15% by mass or more.

Citation Information

Patent Citations

  • Antireflection film of optical parts made of synthetic resin

    JP1994273601A

  • Near-eye display optical module

    JP2017021321A

  • Imidized acrylic polymers

    US4246374A

  • Wide-angle collimating optical device

    US6563638B2

  • Plastic lens, lens unit and method for producing plastic lens

    WO2023074597A1